Cathepsin K in bone and joint diseases - Bromme, Dieter (Henry Stewart Talks, 2007)
Cysteine proteases, Cathepsin family, Expression of cathepsins and their activity, Collagen degradation, Pycnodysostosis, Cathepsin K in osteoporosis, Cathepsin K in arthritis, Mouse model of arthritis